Bifrontal hyperacute extradural hematoma - Gupta, Deepak Kumar; Singh, Karanjit; Mahapatra, AK (Indian Journal of Neurotrauma, 2008)
Bifrontal extradural hematomas are uncommon. A 9 year old girl presented with head injury and inoperable intracranial lesion on early CT scan with normal neurological status. A repeat CT scan revealed development of hyperacute EDH without any further neurological worsening. Patient was operated and evacuation of hematoma was carried out. The patient made complete recovery. The present case report emphasizes the need of repeat CT scanning in all head injuries patients if first scanning is done within 6 hours of injury and discusses the bifrontal extradural hematomas.